ANALISIS FLUKTUASI KURS RUPIAH TERHADAP DOLLAR AMERIKA (1997.1 - 2004.IV) - Anggyatika Mahda Kurnia; Didit Purnomo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2006)
The research aims at analyzing the fluctuation ofRupiah exchange rate against US dollar. Data used in the research are quarterly time series data, namely in period from 1997.1 to 2004.IV. The analysis tools used in this research are multivariate linear regression by Error Correction Model (ECM). The result of this research concluded that the variables of The Rupiah exchange rate, inflation, interest rate of Bank Indonesia and import value has been stationer, only the variable of money supply on which is not stationer.ECM analysis results in the valid model on the Rupiah exchange rate against US dollar. It is showed by the significant ECT value at a=0.05; the regression coefficient value is 0.231835. Based on the classical assumption test, there is not found any problem. Normality test showed that Ut distribution is normal, the model specification test by Ramsey Reset Test showed that the model used is linear. The determination coefficient showed that about 90.5813% of the Rupiah exchange rate against US dollar could be explained by the variables of the model. The result of the t test analysis showed that the significant variable is the money supply (a=10%), inflation (a=l%), import value (a=l%)